ITS-RFLP optimization for dermatophyte identification from clinical sources in Alagoas (Brazil) versus phenotypic methods - Villanueva da Fonseca, Luisa Andrea; Santos Araújo, Maria Anilda; Wanderlei Silva, Denise Maria; de Albuquerque Maranhão, Fernanda Cristina (The Journal of Infection in Developing Countries, 2022)
Introduction: Dermatophytoses are superficial mycoses, and the identification of their etiological agents is routinely performed by culture and microscopic features, which is time-consuming and relies on personnel expertise. Molecular approaches have been developed to provide faster and reliable results; therefore, this study aimed to identify dermatophytes isolated from Alagoas state patients, employing phenotypical and molecular methods. Methodology: Clinical samples for morphological identification were collected from private and public laboratories and cultivated on Sabouraud dextrose agar. DNA extraction was followed by ITS amplicon analysis after restriction enzyme digestion DdeI (ITS-RFLP). Results: Out of fourteen representative strains, ITS-RFLP with DdeI efficiently identified Microsporum canis, Nannizzia gypsea, and Trichophyton rubrum, while species of the complex T. tonsurans/T. mentagrophytes presented the same restriction pattern. After genotyping, 2 T. tonsurans and 1 Microsporum sp. strain were reclassified as T. rubrum. Conclusions: RFLP of ITS-region followed by DdeI digestion produced faster and relatively reliable results than classic methods; however, this method has not been as efficient for closely related dermatophytes cryptic species.